(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The article investigates linguistic basics for teaching the course of the Ukrainian phonetics at the gymnasium as well as defines key points of its phonetic system which are to be highlighted in the contents of linguistic education on the specialized level of teaching.